Zinaida Vissarionovna Ermolyeva at Rostov medical institute - A. Yu. Popova; G. G. Kharseeva; A. E. Volkova; S. V. Shlyk (Медицинский вестник Юга России, 2024)
The article analyzes materials from the State Archive of the Rostov Region about Zinaida Vissarionovna Ermolyeva, an outstanding Soviet microbiologist and epidemiologist, academician of the USSR Academy of Medical Sciences, creator of the first domestic drugpenicillin. Data are provided about her years of study at the Rostov Women's Medical Institute, and the nat the Faculty of Medicine of Don University. Archival materials are considered hat testify to the first stages of her career as a teacher and scientist at the Department of Microbiology of Don University.